Patient Health Questionnaire-9 and Generalized Anxiety Discorders-7: Arabic Version Reliability in Jordan - Yousuf , Mustafa; Harvey, Heather; Al Sharei, Aiman; Albakri, Khaled; Alabdallat, Yasmeen (Jordan Medical Journal, 2022)
Background: Depression and anxiety are common mental disorders that are often missed in primary healthcare settings due to the lack of diagnosis criteria. Using valid and reliable easy-to-use instruments can overcome this problem. Aims: To translate and culturally adapt the Patient Health Questionnaire-9 (PHQ9) and the Generalized Anxiety Disorders-7 (GAD7) instruments into Arabic, determine the reliability of these translated versions, and compare them with previous attempts. Methods: Forward and blind back-translation was used to translate the instruments into Arabic. An online version was created and sent to medical school students at the Hashemite University, Jordan. For each instrument, internal consistency reliability and inter-item correlation were calculated. For each item, the mean, standard deviation, item-total correlation, and value of Cronbach’s alpha if the item was deleted were determined. Analysis was performed using IBM SPSS version 25. Results: There were 256 respondents to the translated instruments. The average age was 18.85 and 61% were females. The alpha for the PHQ9 was 0.876, with an average inter-item correlation of 0.444. Removal of any of the nine items decreased the value of alpha. The GAD7 had an alpha of 0.895 with an average inter-item correlation of 0.551. Deletion of any item decreased the internal consistency reliability of the instrument. Conclusion: Using an efficient translation process that was both accurate and culturally sensitive enabled the construction of Arabic versions of the PHQ9 and the GAD7 scales that had high internal consistency reliability and good inter-item correlation.